The Economics of Production Safety for Customized Product Using 3-D Printer based on Three-Dimensional Printing Industry Promotion Act - Sunho Yoona; Ahreum Hongb; Junseok Hwanga (International Telecommunications Society (ITS), 2018)
Three-Dimensional Printing Industry Promotion Act has been enacted in 2015 based on "Product Liability Act" in Korea. It is believed that Korea enacted "Product Liability Act" in 2002 to make easier for damage cost to be paid to users by reducing the burden of proof. The model used in this paper argues that the social cost of product damage for customized products is determined by sum of attention cost for user and the 3-D1 service provider with the level of existed safety information, and expected damage costs. The equilibrium point can meet optimal point when the level of safety information is same as traditional products. Given six liability rule, the equilibrium point cannot meet social optimal point. So under the exemption in "Three-Dimensional Printing Industry Promotion Act", which is directly related to the customized product using three-dimensional printer, users and the 3-D service provider cannot be expected to minimize their costs.
Keywords: 330